Comparison of the Mayo Endoscopy Score and the Ulcerative Colitis Endoscopy Index of Severity and the Ulcerative Colitis Colonoscopy Index of Severity - Belvis Jiménez, María; Hergueta-Delgado, Pedro; Gómez Rodríguez, Blas; Maldonado Pérez, Belén; Castro Laria, Luisa; Rodríguez-Téllez, Manuel; Morales Barroso, Maria Luisa; Galván Fernández, Maria Dolores; Guerra Veloz, Maria; Jiménez García, Victoria Alejandra; Romero-Castro, Rafael; Benítez-Roladán, Antonio; Castro Márquez, Cristina; Aparcero López, Reyes; Garrido-Serrano, Antonio; Caunedo-Álvarez, Ángel; Argüelles-Arias, Federico (Endoscopy International Open, 2021)
Background and study aims: Endoscopy plays an essential role in managing patients with ulcerative colitis (UC), as it allows us to visualize and assess the severity of the disease. As such assessments are not always objective, different scores have been devised to standardize the findings. The main aim of this study was to assess the interobserver variability between the Mayo Endoscopy Score (MES), Ulcerative Colitis Endoscopy Index of Severity (UCEIS) and Ulcerative Colitis Colonoscopy Index of Severity (UCCIS) analyzing the severity of the endoscopic lesions in patients with ulcerative colitis.Patients and methods: This was a single-cohort observational study in which a colonoscopy was carried out on patients with UC, as normal clinical practice, and a video was recorded. The results from the video were classified according to the MES, UCEIS and UCCIS by three endoscopic specialists independently, and they were compared to each other. The Mayo Endoscopy Score (MES) was used to assess the clinical situation of the patient. The therapeutic impact was analyzed after colonoscopy was carried out.Results: Sixty-seven patients were included in the study. The average age was 51 (SD ± 16.7) and the average MES was 3.07 (SD ± 2.54). The weighted Kappa index between endoscopists A and B for the MES was 0.8; between A and C 0.52; and between B and C 0.49. The intraclass correlation coefficient for UCEIS was 0.92 among the three endoscopists (CI 95 %: 0.83–0.96) and 0.96 for UCCIS among the three endoscopists (CI 95 % 0.94–0.97). A change in treatment for 34.3 % of the patients was implemented on seeing the results of the colonoscopy.Conclusions: There was an adequate, but not perfect, correlation between the different endoscopists for MES, UCEIS, UCCIS. This was higher with the last two scores. Thus, there is still some subjectivity to be minimized through special training, on assessing the seriousness of the endoscopic lesions in patients with UC.